Magneto-Biostratigraphy, Paleobathymetry, and Basin Subsidence History of Taiwan Coastal Range - Larry Syu-Heng Lai; Rebecca J. Dorsey; Chorng-Shern Horng; Wen-Rong Chi; Kai-Shuan Shea; Jiun-Yee Yen (Zenodo, 2022)
This repository is the supplementary dataset used for sedimentary basin analysis in the Taiwan's Coastal Range. The results are about to be published in apaper titled "Extremely rapid up-and-down motions of island arc crust during arc-continent collision" by Lai et al. at the journal Communications Earth & Environment. FourMicrosoft Excel spreadsheets include sample information,data,and analyticresults of rock paleomagnetism, calcareous nannoplankton biostratigraphy, planktonic foraminifera biostratigraphy, foraminifera-based paleobathymetry estimates, and basin subsidence analysis. The Rscripts developed forthese analyses are stored in another Zenodo repository: https://doi.org/10.5281/zenodo.5823613 Citation: If you consider using these scripts and data, please cite the following references: Lai, L.S.-H., Dorsey, R.J., Horng, C.-S., Chi, W.-R., Shea, K.-S., and Yen, J.-Y. (Accepted) Extremely rapid up-and-down motions of island arc crust during arc-continent collision. Communications Earth & Environment . Lai, L.S.-H., Dorsey, R.J., Horng, C.-S., Chi, W.-R., Shea, K.-S., and Yen, J.-Y. (2021) Polygenetic mélange in retrowedge foredeep of an active arc-continent collision, Coastal Range of eastern Taiwan. Sedimentary Geology , v. 418, 105901. https://doi.org/10.1016/j.sedgeo.2021.105901